A ternary sulfide compound heterojunction catalytic material and its synthesis method and application

By constructing Zn2In2S5/Bi19S27Br3 Z-type heterojunction catalytic material, the problem of low charge transfer efficiency of ternary chalcogenide compounds in the photocatalytic process is solved, the effect of efficient degradation of organic pollutants is achieved, and the stability and stability of the material are improved. Reusability.

CN119140127BActive Publication Date: 2025-01-21中国市政工程西北设计研究院有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411602380.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-21
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

During the photocatalysis process, existing ternary chalcogen compounds have problems such as low charge transfer efficiency, frequent carrier recombination and low basal sulfur atomic activity, which is difficult to meet the requirements of photocatalytic activity and pollutant degradation efficiency.

Method used

By constructing Zn2In2S5/Bi19S27Br3 Z-type heterojunction catalytic materials, the intrinsic spontaneous polarization of Zn2In2S5 and the negative conduction band position of Bi19S27Br3 are used to improve the space interface charge separation and transfer efficiency and enhance the photocatalytic activity.

Benefits of technology

Efficient degradation of organic pollutants, especially bisphenol A, under visible light irradiation was achieved, significantly improving the photocatalytic activity and the stability and reusability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140127B_ABST
    Figure CN119140127B_ABST
Patent Text Reader

Abstract

The invention discloses a ternary sulfide compound heterojunction catalytic material and its synthesis method and application, belonging to the field of photocatalysts. Synthesis method: dissolve ZnCl2 and InCl3·4H2O in an ethanol aqueous solution, stir, add thioacetamide to the mixed solution and continue stirring, then subject the solution to a hydrothermal reaction, cool, centrifuge, wash, and then dry to constant weight to obtain the material Zn2In2S5; disperse Zn2In2S5, thiourea, 1-hexadecyl-3-methylimidazolium bromide, and Bi(NO3)3·5H2O in anhydrous ethanol, subject the mixture to a hydrothermal reaction after ultrasonic dispersion, cool, centrifuge, wash, and then dry to constant weight to obtain the powder material Zn2In2S5 / Bi 19 S 27 Br3. The present invention greatly improves the photocatalytic activity through the construction of a heterojunction, realizes the degradation of pollutants, and has the characteristics of good stability and reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalysts, and in particular relates to a ternary sulfide compound heterojunction catalytic material and a synthesis method and application thereof. Background Art

[0002] In recent years, Zn m In2S 3+m As a new type of layered ternary chalcogenide, Zn (m=1-5) has attracted wide attention in the field of photocatalysis because it can optimize the electronic structure by adjusting the ratio of zinc (Zn) and indium (In) and has a suitable band gap. Due to its atomic layered structure and suitable band gap structure, it has become a hot spot for photocatalytic degradation of pollutants. m In2S 3+m The layered structure of Zn can shorten the diffusion distance of photogenerated carriers, providing a large specific surface area and abundant active sites for photochemical reactions. m In2S 3+m The band structure of can be tuned by adding S-Zn-S layers, thereby changing the redox potential.

[0003] ZnIn2S4 has the advantages of selective C-H bond activation and dehydrogenation conversion of organic substrates due to its -SH surface active sites, high physicochemical stability and suitable band structure. Taking advantage of these advantages, ZnIn2S4 has great potential in overcoming slow charge transfer. So far, various strategies have been developed to promote charge migration on ZnIn2S4, including heterojunction structures, impurity doping and co-catalyst loading. However, these modification methods mainly affect the charge separation efficiency of the surface or active site regions, and their treatment effects are relatively limited for the internal regions of the material where carrier recombination frequently occurs, that is, the bulk region. In addition, due to the limited charge transfer of the redox process, the main basal plane sulfur atoms show lower activity than the edge sulfur sites. Therefore, this requires solving the problem of bulk surface charge separation and spatial charge transfer at the same time.

[0004] With the development of promoting the separation of photogenerated carriers, constructing polarization electric fields in non-centrosymmetric semiconductors has become one of the effective strategies. Compared with the traditional zinc indium sulfide (ZnIn2S4) material, Zn2In2S5 has the most suitable conduction band level and band gap for the photocatalytic kinetics of pollutant degradation. At the same time, its inherent spontaneous polarization along the

[001] crystal plane can promote charge separation in the bulk phase. However, it still has the disadvantages of easy aggregation of electron-hole pairs and rapid recombination of photogenerated carriers, and the photocatalytic activity of a single photocatalyst still does not meet the requirements.

[0005] The construction of heterojunctions has been shown to be an effective strategy to improve the separation and transfer of photogenerated carriers at spatial interfaces, thereby enhancing the photocatalytic activity of materials. 19 S 27 As a metal halide, Br3 has excellent conductivity, high light absorption ability and sufficient negative conduction band (CB) position, which ensures that the photoexcited electrons have strong reduction ability. These inherent properties make Bi 19 S 27 Br3 has broad application prospects in pollutant degradation research. 19 S 27 The narrow band gap of Br3 (about 1.48 eV) leads to a high recombination rate of photogenerated charge carriers, which seriously affects the photocatalytic performance.

[0006] Therefore, the present invention develops a method for synthesizing a ternary chalcogenide heterojunction catalytic material, and synthesizes a Zn2In2S5 / Bi 19 S 27 Br3 Z-type heterojunction, photodegradation of pollutant bisphenol A under visible light irradiation. Summary of the invention

[0007] The purpose of the present invention is to provide a method for synthesizing a ternary sulfide compound heterojunction catalytic material, so as to prepare a ternary sulfide compound heterojunction catalytic material with stronger visible light absorption, higher bulk surface and space charge separation efficiency, better stability, reusability, and the ability to achieve photocatalytic degradation of organic pollutants by a simple process.

[0008] Another object of the present invention is to provide a ternary chalcogenide heterojunction catalytic material.

[0009] The third object of the present invention is to provide an application of a ternary chalcogenide heterojunction catalytic material.

[0010] The technical solution of the present invention is: (one)

[0012] A method for synthesizing a ternary chalcogenide heterojunction catalytic material comprises the following steps:

[0013] A. Dissolve a certain molar ratio of ZnCl2 and InCl3·4H2O in an ethanol aqueous solution, stir, add an appropriate amount of thioacetamide to the mixed solution and continue stirring, then subject the solution to a hydrothermal reaction, cool to room temperature, collect the resulting product by centrifugation, wash, and then dry to constant weight to obtain the material Zn2In2S5;

[0014] B. Disperse a certain mass ratio of Zn2In2S5, thiourea, 1-hexadecyl-3-methylimidazolium bromide, and Bi(NO3)3·5H2O in anhydrous ethanol, perform ultrasonic dispersion at a frequency of 80-100 kHz, and then perform hydrothermal reaction on the mixture. After cooling to room temperature, centrifuge, wash, and then dry to constant weight to obtain a gray-black powder material Zn2In2S5 / Bi 19 S 27 Br3 is a ternary chalcogenide heterojunction catalytic material.

[0015] As a further improvement of the present invention, in step A, the molar ratio of ZnCl2, InCl3·4H2O and thioacetamide is 1:1-2:2.5-4.

[0016] As a further improvement of the present invention, in step A, the hydrothermal reaction temperature is 140-180° C., and the hydrothermal reaction time is 10-14 h.

[0017] As a further improvement of the present invention, in step B, the mass ratio of Zn2In2S5, thiourea, 1-hexadecyl-3-methylimidazolium bromide, and Bi(NO3)3·5H2O is 50-100:4-5:20:1.

[0018] As a further improvement of the present invention, in step B, the hydrothermal reaction temperature is 120-140° C., and the hydrothermal reaction time is 10-14 h. (two)

[0020] A ternary sulfide compound heterojunction catalytic material is prepared by the synthesis method of the ternary sulfide compound heterojunction catalytic material.

[0021] Zinc indium sulfide (Zn m In2S 3+m ) is a ternary chalcogenide. Its band structure can be adjusted by changing the ratio of zinc to indium. m In2S 3+m Coupling with semiconductors with matching band gaps to construct heterojunctions is an effective strategy to promote charge separation and improve light absorption, thereby improving photocatalytic performance. The main basal plane sulfur atoms in traditional zinc indium sulfide (ZnIn2S4) materials show lower activity than edge sulfur sites, resulting in a higher bulk carrier recombination rate. Zn2In2S5 has unique electronic properties compared to traditional ZnIn2S4 materials, and the presence of inherent spontaneous polarization can promote charge separation in the bulk phase. In addition, the matching energy level structure and complementary visible light absorption enable the constructed Z-type heterostructure to transfer the photogenerated electrons of Zn2In2S5 across the heterojunction interface to Bi 19 S 27On Br3, the recombination of electron-hole pairs is reduced, which greatly enhances the efficiency of spatial interface charge transfer.

[0022] Compared with the valence band of Zn2In2S5 (~1.95 eV), Bi 19 S 27 The valence band position of Br3 is more negative (~ 0.18 eV), even close to the conduction band position of Zn2In2S5 (~ -0.56 eV). 19 S 27 The establishment of a direct Z-type heterojunction between Br3 and Zn2In2S5 materials can improve the separation efficiency of spatial interface charge carriers and maximize the reduction ability of excited electrons. (three)

[0024] The application of a ternary chalcogenide heterojunction catalytic material in the photocatalytic degradation of organic pollutants. When the material is excited by visible light, the photogenerated electron-hole pairs generated have higher redox ability, so that they react with water molecules and dissolved oxygen to generate a variety of active oxidizing substances to efficiently degrade pollutants.

[0025] Furthermore, organic pollutants include bisphenol A, atrazine, carbamazepine, tetracycline, rhodamine B, etc. Preferably, the Zn2In2S5 / Bi 19 S 27 Br3 has an exceptionally good degradation effect on bisphenol A under photocatalytic conditions. On the one hand, the photocatalytic material Zn2In2S5 / Bi 19 S 27 Br3 is photoexcited under visible light to generate photogenerated electrons and photogenerated holes. The matching energy level positions enable the photogenerated electrons in the conduction band of Zn2In2S5 to transfer across the heterojunction interface to Bi 19 S 27 Br3 valence band, this Z-type charge transport mechanism not only promotes carrier separation, but also retains strong redox ability and promotes spatial charge transfer. On the other hand, in the presence of the inherent spontaneous polarization electric field, the photogenerated electron-hole pairs on the surface of the Zn2In2S5 material are further induced to continuously generate, which promotes the bulk surface charge separation, thereby significantly improving the charge separation efficiency. Ultimately, the pollutants are oxidized by surface active oxygen or hydroxyl groups and holes, and finally generate water and carbon dioxide.

[0026] The beneficial effect of the present invention is that the present invention constructs a heterojunction to connect Zn2In2S5 and Bi 19 S 27 Br3 composite, constructing a ternary chalcogenide heterojunction catalytic material—Zn2In2S5 / Bi with stronger carrier separation ability on the bulk surface and space interface, light absorption range covering the entire visible spectrum, and higher catalytic activity.19 S 27 Br3. By constructing a heterojunction, Zn2In2S5 and the full visible spectrum absorption material Bi 19 S 27 Br3 composite, successfully realized Zn2In2S5 / Bi 19 S 27 The photogenerated electron-hole pairs of Br3 composite photocatalytic nanomaterials are separated at the heterojunction interface, avoiding the electron-hole recombination problem in the band gap of a single nanomaterial. The matching energy level position arrangement enables the two to accelerate the migration and separation of photogenerated charges. The construction of the heterojunction more effectively enhances the charge separation and electron transfer at the heterojunction interface, greatly improving the photocatalytic activity. 19 S 27 The Br3 photocatalytic system achieves effective pollutant degradation and has the characteristics of simple synthesis method, good stability and reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Zn2In2S5 / Bi prepared in Example 1 of the present invention 19 S 27 SEM image of Br3;

[0028] Figure 2 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 UV diffuse reflectance absorption spectrum of Br3;

[0029] Figure 3 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 Fourier infrared spectrum of Br3;

[0030] Figure 4 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 Performance comparison of Br3 photocatalytic degradation of bisphenol A;

[0031] Figure 5 Zn2In2S5 / Bi prepared in Example 1 of the present invention 19 S27 Degradation diagram of the reusable experiment of Br3 photocatalytic degradation of bisphenol A. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0033] Embodiment 1,

[0034] A method for synthesizing a ternary chalcogenide heterojunction catalytic material comprises the following steps:

[0035] A. Dissolve 0.8mmol ZnCl2 and 0.8mmol InCl3·4H2O in 50% volume fraction ethanol aqueous solution. After vigorous stirring for 30 minutes, add 2mmol thioacetamide to the mixed solution and continue stirring. Then transfer the solution to a 100mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours. After cooling to room temperature, collect the obtained product by centrifugation, wash it alternately with ethanol and distilled water for 6 times, and then dry it in an oven at 60°C to constant weight to obtain the material Zn2In2S5.

[0036] B. Disperse 0.4 g Zn2In2S5, 0.035 g thiourea, 0.16 g 1-hexadecyl-3-methylimidazolium bromide and 0.008 g Bi(NO3)3·5H2O successively in 50 mL anhydrous ethanol. After ultrasonic dispersion at 80 kHz for 30 min, pour the mixture into a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at a temperature of 130 ° C for 12 hours. After cooling to room temperature, centrifuge and wash with ethanol and ultrapure water for 3 times each. Then, dry at 60 ° C to constant weight to obtain a gray-black powder material Zn2In2S5 / Bi 19 S 27 Br3 is a ternary chalcogenide heterojunction catalytic material.

[0037] Figure 1 Zn2In2S5 / Bi prepared in Example 1 of the present invention 19 S 27 Scanning electron microscope image of Br3. Figure 1 As shown, Zn2In2S5 and Bi 19 S 27 Br3 nanosheets stacked on each other to form a nanoflower structure, which provides more exposed area and offers the potential for enhanced visible light absorption.

[0038] Comparative Example 1

[0039] Prepare only Zn2In2S5:

[0040] 1.0 mmol ZnCl2 and 1.0 mmol InCl3·4H2O were dissolved in 50% volume fraction ethanol aqueous solution. After vigorous stirring for 30 minutes, 2.5 mmol thioacetamide was added to the mixed solution and stirring was continued. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 140°C for 14 hours. After cooling to room temperature, the product was collected by centrifugation, washed alternately with ethanol and distilled water for 6 times, and then dried in an oven at 60°C to constant weight to obtain the catalytic material Zn2In2S5.

[0041] Comparative Example 2

[0042] Only Bi 19 S 27 Br3:

[0043] 0.032g thiourea, 0.16g 1-hexadecyl-3-methylimidazolium bromide, and 0.008g Bi(NO3)3·5H2O were dispersed in 50mL anhydrous ethanol successively. After ultrasonic dispersion at a frequency of 100kHz for 30min, the mixture was poured into a 100mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at a temperature of 140°C for 10 hours. After cooling to room temperature, the mixture was centrifuged and washed with ethanol and ultrapure water for 3 times each, and then dried at 60°C to constant weight to obtain a gray-black powder catalytic material Bi 19 S 27 Br3.

[0044] Embodiment 2,

[0045] A method for synthesizing a ternary chalcogenide heterojunction catalytic material comprises the following steps:

[0046] A. Dissolve 0.8 mmol ZnCl2 and 1.6 mmol InCl3·4H2O in 50% volume fraction ethanol aqueous solution. After vigorous stirring for 30 minutes, add 3.2 mmol thioacetamide to the mixed solution and continue stirring. Then transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 140°C for 14 hours. After cooling to room temperature, collect the product by centrifugation, wash it alternately with ethanol and distilled water for 6 times, and then dry it in an oven at 60°C to constant weight to obtain the material Zn2In2S5.

[0047] B. Disperse 0.4 g Zn2In2S5, 0.032 g thiourea, 0.16 g 1-hexadecyl-3-methylimidazolium bromide and 0.008 g Bi(NO3)3·5H2O successively in 50 mL anhydrous ethanol. After ultrasonic dispersion at 90 kHz for 30 min, pour the mixture into a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at a temperature of 140°C for 10 hours. After cooling to room temperature, centrifuge and wash with ethanol and ultrapure water for 3 times each. Then, dry at 60°C to constant weight to obtain a gray-black powder material Zn2In2S5 / Bi 19 S 27 Br3 is a ternary chalcogenide heterojunction catalytic material.

[0048] Embodiment 3,

[0049] A method for synthesizing a ternary chalcogenide heterojunction catalytic material comprises the following steps:

[0050] A. Dissolve 1.0 mmol ZnCl2 and 1.0 mmol InCl3·4H2O in 50% volume fraction ethanol aqueous solution. After vigorous stirring for 30 minutes, add 2.5 mmol thioacetamide to the mixed solution and continue stirring. Then transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 10 hours. After cooling to room temperature, collect the product by centrifugation, wash it alternately with ethanol and distilled water for 6 times, and then dry it in an oven at 60°C to constant weight to obtain the material Zn2In2S5.

[0051] B. Disperse 0.8 g Zn2In2S5, 0.04 g thiourea, 0.16 g 1-hexadecyl-3-methylimidazolium bromide and 0.008 g Bi(NO3)3·5H2O successively in 50 mL anhydrous ethanol. After ultrasonic dispersion at 100 kHz for 30 min, pour the mixture into a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 120 °C for 14 hours. After cooling to room temperature, centrifuge and wash with ethanol and ultrapure water for 3 times each. Then, dry at 60 °C to constant weight to obtain a gray-black powder material Zn2In2S5 / Bi 19 S 27 Br3 is a ternary chalcogenide heterojunction catalytic material.

[0052] 1. Evaluation of photocatalytic degradation performance

[0053] The catalytic materials prepared in Example 1 and Comparative Examples 1 and 2 were subjected to photodegradation experiments of bisphenol A to evaluate the photocatalytic performance of the synthesized Zn2In2S5 / Bi 19S 27 Photodegradation performance of Br3 catalytic material under PMS activation. The specific experiment is as follows:

[0054] The photodegradation process was carried out in a 250 ml custom double-walled quartz beaker with a cooling water circulation system to keep the reaction temperature constant. The light source was a 300 W xenon lamp (420 nm < λ < 800 nm) with an average light intensity of 200 mW / cm 2 . Before the reaction started, 50 mg of the catalytic material was dispersed in a bisphenol A solution (10 mg / L, 100 mL), and the pH value was controlled at about 7 with 0.1 M hydrochloric acid or sodium hydroxide solution. The suspension was stirred continuously during the entire reaction. A dark adsorption experiment was performed 30 minutes before illumination to achieve the adsorption-desorption equilibrium between bisphenol A and the photocatalyst. Then, 1 mM PMS was added. During the photodegradation process, 1 mL of the reaction solution was taken out at regular intervals and then passed through a 0.22 μm filter to prepare for ultra-high performance liquid chromatography analysis. The mobile phase was acetonitrile and ultrapure water in a volume ratio of 50:50, and the detection wavelength was 278 nm. The relative concentration (C / C0) was used to calculate the degradation efficiency.

[0055] Figure 2 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 The ultraviolet diffuse reflection absorption spectrum of Br3. Figure 2 As shown, the light absorption cutoff edge of single Zn2In2S5 is about 450nm, indicating that its absorption of visible light is weak, while Bi 19 S 27 Br3 exhibits full spectrum absorption in the entire ultraviolet and visible light regions. 19 S 27 Br3, it can be seen that Bi 19 S 27 The loading of Br3 effectively retains the absorption tail peak intensity of the material and significantly enhances the light absorption in the absorption band > 450 nm, effectively improving the visible light capture efficiency of the composite material.

[0056] Figure 3 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 Fourier infrared spectrum of Br3. For Zn2In2S5, at 1426 cm -1、1601 cm -1 and 3336 cm -1 The broad peaks at 656 cm -1 The peak corresponds to the stretching vibration of the Zn / In-S bond. 19 S 27 Br3, at 763cm -1 The peak at 1323 cm -1 、1568 cm -1 and 3247 cm -1 The broad peak at corresponds to the surface adsorption of water and hydroxyl molecules. 19 S 27 The main typical absorption peaks of Br3 are present in Zn2In2S5 / Bi 19 S 27 Br3 sample, which further indicates that Zn2In2S5 / Bi 19 S 27 Successful synthesis of Br3 composite catalyst.

[0057] Figure 4 Zn2In2S5 / Bi prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 19 S 27 Br3, Zn2In2S5, Bi 19 S 27 Comparison of the photocatalytic degradation performance of bisphenol A by Br3. Figure 4 As shown in the experimental results, under the conditions of 0.5 g / L catalytic material dosage, 10 mg / L initial bisphenol A concentration and room temperature, single Zn2In2S5 / PMS and Bi 19 S 27 The degradation efficiency of Br3 / PMS system for bisphenol A was 42.55% and 87.69%, respectively, while that of Zn2In2S5 / Bi 19 S 27 The removal rate of bisphenol A by the Br3 / PMS system reached 99.79%, which means that Bi 19 S 27 The loading of Br3 enables the composite material to utilize more visible light. At the same time, the construction of the Z-type heterojunction effectively improves the interfacial charge transfer of photogenerated carriers and suppresses the in-situ recombination of photogenerated electron-hole pairs in two single photocatalysts.

[0058] 2. Continuous degradation experiment

[0059] Zn2In2S5 / Bi prepared in Example 1 19 S 27After the first degradation reaction of Br3 was completed, the post-reaction solution was centrifuged and washed, and the recovered catalytic material was dried in a freeze dryer for 48 hours, and then put into the reactor again for the next degradation experiment. Except for the material, the other degradation reaction conditions were consistent with the setting procedures of the first photocatalytic degradation performance evaluation experiment; after the second reaction was completed, the above steps were repeated and three degradation experiments were carried out.

[0060] Figure 5 Zn2In2S5 / Bi prepared in Example 1 of the present invention 19 S 27 The degradation diagram of the reusable experimental degradation of bisphenol A by Br3 photocatalysis. Figure 5 As shown in the figure, the degradation efficiency of bisphenol A was above 98% in three consecutive degradation experiments, which indicates that Zn2In2S5 / Bi 19 S 27 The photocatalytic activity of the Br3 catalytic material remained good after three cycles.

[0061] The present invention combines Zn2In2S5 material and Bi 19 S 27 Combined with Br3 materials, the inherent electronic properties of Zn2In2S5 promote bulk charge transfer. The full visible spectrum absorption and the existence of the Z-type heterojunction effectively improve the efficiency of light capture and spatial interface separation, making the ternary chalcogenide heterojunction material able to efficiently degrade pollutants under visible light irradiation, and has the characteristics of good stability in the aqueous phase and recyclability.

Claims

1. A method for synthesizing a ternary chalcogenide heterojunction catalytic material, characterized in that The following steps are involved: A. Dissolve ZnCl2 and InCl3·4H2O in an ethanol aqueous solution, stir, add thioacetamide to the mixed solution and continue stirring, then subject the solution to a hydrothermal reaction, cool to room temperature, collect the resulting product by centrifugation, wash, and then dry to constant weight to obtain the material Zn2In2S5; B. Disperse Zn2In2S5, thiourea, 1-hexadecyl-3-methylimidazolium bromide and Bi(NO3)3·5H2O in anhydrous ethanol, perform hydrothermal reaction on the mixture after ultrasonic dispersion, cool to room temperature, centrifuge, wash, and then dry to constant weight to obtain powder material Zn2In2S5 / Bi 19 S 27 Br3 is a ternary chalcogenide heterojunction catalytic material.

2. The method for synthesizing a ternary chalcogenide heterojunction catalytic material according to claim 1, characterized in that: In step A, the molar ratio of ZnCl2, InCl3·4H2O and thioacetamide is 1:1-2:2.5-4.

3. The method for synthesizing a ternary chalcogenide heterojunction catalytic material according to claim 1, characterized in that: In step A, the hydrothermal reaction temperature is 140-180° C., and the hydrothermal reaction time is 10-14 h.

4. The method for synthesizing a ternary chalcogenide heterojunction catalytic material according to claim 1, characterized in that: In step B, the mass ratio of Zn2In2S5, thiourea, 1-hexadecyl-3-methylimidazolium bromide, and Bi(NO3)3·5H2O is 50-100:4-5:20:

1.

5. The method for synthesizing a ternary chalcogenide heterojunction catalytic material according to claim 1, characterized in that: In step B, the hydrothermal reaction temperature is 120-140° C., and the hydrothermal reaction time is 10-14 h.

6. A ternary chalcogenide heterojunction catalytic material, characterized in that: The ternary sulfide compound heterojunction catalytic material is prepared by the synthesis method of any one of claims 1 to 5.

7. Use of the ternary chalcogenide heterojunction catalytic material according to claim 6 in photocatalytic degradation of organic pollutants.

8. The use of a ternary chalcogenide heterojunction catalytic material in photocatalytic degradation of organic pollutants according to claim 7, characterized in that: The organic pollutants include bisphenol A.

Citation Information

Patent Citations

  • Heterojunction composite material and preparation method and application thereof

    CN116713010A

  • Bi19S27Br3 / CoAl-LDH composite photocatalyst as well as preparation method and application thereof

    CN117258811A